Sex hormone binding globulin in breast cancer - Naik S L, Dayalu (Springer-Verlag, 2008)
The present study was undertaken to determine the significance of sex hormone binding globulin, the major and specific binding protein for testosterone and estradiol, in breast cancer. Among breast cancer patients, lower serum levels of Sex hormone binding globulin and higher levels of testosterone were observed. Sex hormone binding globulin showed an inverse relationship with testosterone and total cholesterol, and a direct relation with HDL-cholesterol. By the western blot analyses, Sex hormone binding globulin was detected in all biological samples that we examined. In the breast tumor tissue sections, immuno-staining for Sex hormone binding globulin was confined in cell cytoplasm and 29% cases were positive, which showed no association with the investigated prognostic markers of breast cancer such as ER and HER-2/neu over-expression. In this study, decreased circulating levels of Sex hormone binding globulin in breast cancer patients possibly indicate higher bioavailable estrogens.